2002
DOI: 10.1039/b110108k
|View full text |Cite
|
Sign up to set email alerts
|

Structure-reactivity relationships in the photoreduction of n,π*-excited ketones and azoalkanes: the effect of reaction thermodynamics, excited-state electrophilicity, and antibonding character in the transition state

Abstract: The reaction enthalpies for the photoreduction of n,pi*-excited states (acetone, benzophenone, 2.3-diazabicyclo[2.2.2]oct-2-ene, and a 2,3-diazabicyclo[2.2.1]hept-2-ene derivative) by model hydrogen donors (methanol and dimethylamine) were calculated on the basis of a critically evaluated data set of bond dissociation energies for donors and reduced acceptors. These were compared with the observed photoreactivity, which can be assessed through quenching rate constants of the excited states by hydrogen donors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 65 publications
3
29
0
Order By: Relevance
“…The more negative ρ values for triplet ketones are in line with the participation of charge transfer (exciplex formation) in the quenching. In contrast, the variance in ρ values between singlet‐excited DBO and the tert ‐butoxyl radical must be related to polar effects in the direct hydrogen abstraction process (2, 13, 18, 33), because exciplexes or ground‐state charge transfer complexes are not postulated for these two reactive species. Such philicity effects are commonly understood in terms of contributions of polar resonance structures in the transition state (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The more negative ρ values for triplet ketones are in line with the participation of charge transfer (exciplex formation) in the quenching. In contrast, the variance in ρ values between singlet‐excited DBO and the tert ‐butoxyl radical must be related to polar effects in the direct hydrogen abstraction process (2, 13, 18, 33), because exciplexes or ground‐state charge transfer complexes are not postulated for these two reactive species. Such philicity effects are commonly understood in terms of contributions of polar resonance structures in the transition state (Scheme 1).…”
Section: Resultsmentioning
confidence: 99%
“…Such philicity effects are commonly understood in terms of contributions of polar resonance structures in the transition state (Scheme 1). The polar structure contributes to a different extent for the excited azoalkane versus the tert ‐butoxyl radical, owing to the nature of the abstracting atoms (N versus O) and it has in fact been previously suggested that the excited azo chromophore is a less electrophilic species, implying a lower contribution of the polar structure (in which the abstracting atom bears a partial negative charge) (33). Scrutiny of the results of high‐level ab initio calculations on the hydrogen abstraction of pyrazoline (as a model for DBO) from methylene chloride supports the view of a low degree of charge separation in the transition state (N=N–H–CHCl 2 ) (42), because the partial charges on the azoalkane, the hydrogen to be transferred, and the dichloromethyl moiety are very small and amount to –0.09, +0.24 and –0.15, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations